A Case Study of Competition Policy and Consumer Protection in India - Sharma, Neetu (Gyan Management Journal, 2014)
Consumers play a vital role in the economic system of a nation because in the absence of effective demand that emanates from them, the economy virtually collapses. A welfare State preserves the interests of its citizens. This protective role of the State depends upon the social activity it is protecting. The criminal proclivity is eliminated by punishing the offender through the penal law of the country. Similarly, the civil breaches and distortions are taken care ofby various civil laws including imposition of liability under the law of torts. Hpwever, we need to tackle the issues associated with consumers with a different perspective and framework. The Indian Parliament enacted the Consumer Protection Act, 1986 and amended it from time to time to meet the contemporary requirements. Mahatma Gandhi said, ’’A consumer is the most important visitor on our premises. He is not dependent on us, we are on him. He is not an interruption to our work; he is the purpose of it. We are not doing a favour to a consumer by giving him an opportunity. He is doing us a favour by giving us opportunity ta serve him. But, of late, unfortunately cheating by way of overcharging, black marketing, misleading advertisements, etc has become the_common practice of greedy sellers and manufacturers to make unreasonable profits. In this context, it is the duty of the government to confer some rights on consumers to safeguard their interests.